PELAKSANAAN FUNGSI PEMASYARAKATAN PADA LAPAS KELAS IIA PEKANBARU - Ramadona, Sarah; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The implementation function of correctional in a correctional institution class IIA Pekanbaru is based on act No. 12 year 1999 about correctional. But the practice it is not running optimal yet because the condition of the correctional institutioan that over capacity and the number of officers who do not fit with the standards. This research aims to know the implementation function of correctional in a correctional institution class IIA Pekanbaru. The concept of the theory used in this research adopted actuating theory from some experts.This research using qualitative descriptive method with data collection techniques observation, interview and documentation. Researcher tried to express the fact according to the reality without intervention the real condition.From the data analysis in qualitative descriptive can be seen that the implementation function of correctional in a correctional institution class IIA Pekanbaru has not done well. Activities that will stand have not been able to touch the convict to be better. In this research known factors that affect the implementation is human resources, budget, infrastructure, cooperation and the convict.Key word : actuating, correctional institution, guidance